Petro physical parameter studies for characterization of gas reservoir of Narsingdi gas field, Bangladesh - Towfiqul Islam, Abu Reza Md.; Islam, Md.; Tasnuva, Anjum; Biswas, Raman; Jahan, Khurshida (International Journal of Advanced Geosciences, 2014)
The study focused on quantitative analysis of petrophysical parameters to characterize the reservoir of Narsingdi Gas Field, Bangladesh using well log data. 12 permeable zones were identified, out of which 5 zones were gas-bearing. Shale volume of those zones were averaged at ranged from 14% to 25% indicate reservoir consists of sand dominated lithology and less influence the water saturation for the study well. Porosity of these zones were averaged as 27 % which was within the ranged for very good gas accumulation. Water saturation values were less than 35 % which calculated by using three equations. Gas saturation values were more than 65 % revealed that high gas accumulation in these gas reservoirs. Permeability was averaged at ranged from 32 mD to 55 mD which was within limit for good gas accumulation. Bulk volume of water was averaged at ranged from 0.030 to 0.038 indicate fine grained sand occupied by gas reservoirs were more or less at irreducible water condition. Gas was moveable as indicated by gas moveability index < 0.7. The study suggests that gas reservoir is potential for gas production and accumulation. The study results will contribute in future gas field development programme. Keywords: Gas Moveability Index, Narsindhi Gas Field, Petrophysical Parameter, Reservoir Potential and Well Log Data.